A Man with an Umbilicated Papule of the Hand: What Is Your Diagnosis? - Deba P. Sarma; Meredith Cox; Paige Walter; William Crisler; Christopher Huerter (Case Reports in Medicine)
Introduction. Ecthyma contagiosum is a zoonotic disease caused by the parapoxvirus that causes “sore mouth” in sheep and goats and orf in human. Case Presentation. A 61-year-old sheep farmer presented with a painful non-pruritic lesion on the left hand that had been present for approximately 5 weeks. Physical examination demonstrated a 1 cm pearly, umbilicated papule with raised borders. A biopsy showed an asymmetrical nodule with parakeratotic crust and acanthosis with thin epidermal strands extending deeply in the underlying dermis. Marked edema, capillary proliferation and extensive lymphocytic infiltration was also present. One red intranuclear inclusion was identified in an epidermal keratinocyte. A diagnosis of human orf (ecthyma contagiosum) was made. Conclusion. Infected sheep and freshly vaccinated sheep or goats are the reservoir for human infection. After an incubation period of 3–7 days, parapoxvirus infections produce 1–3 painful lesions measuring 1-2 cm in diameter. The natural history of the disease is complete resolution and no treatment is indicated. Prevention of echthyma contagiosum in ruminants through vaccination is thought to be the best way to control infection.